2016
DOI: 10.1002/rmv.1903
|View full text |Cite
|
Sign up to set email alerts
|

Lujo viral hemorrhagic fever: considering diagnostic capacity and preparedness in the wake of recent Ebola and Zika virus outbreaks

Abstract: Lujo virus is a novel Old World arenavirus identified in Southern Africa in 2008 as the cause of a viral hemorrhagic fever (VHF) characterized by nosocomial transmission with a high case fatality rate of 80% (4/5 cases). Whereas this outbreak was limited, the unprecedented Ebola virus disease outbreak in West Africa, and recent Zika virus disease epidemic in the Americas, has brought into acute focus the need for preparedness to respond to rare but potentially highly pathogenic outbreaks of zoonotic or arthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The 2014–2016 outbreak of EBOV in West Africa underscores the challenges of controlling hemorrhagic fever viruses with profound impacts on human health (Simulundu et al, 2016). Deciphering the interplay between virus and host is not only paramount to understanding mechanisms of pathogenesis but may aid the development of antivirals.…”
Section: Discussionmentioning
confidence: 99%
“…The 2014–2016 outbreak of EBOV in West Africa underscores the challenges of controlling hemorrhagic fever viruses with profound impacts on human health (Simulundu et al, 2016). Deciphering the interplay between virus and host is not only paramount to understanding mechanisms of pathogenesis but may aid the development of antivirals.…”
Section: Discussionmentioning
confidence: 99%
“…The nosocomial transmission in this outbreak indicated that LUJV caused human-to-human transmission. Since then, patients with LUJV infection have never been reported, and LUJV has never been detected in any animal species ( 5 , 6 ). Although LUJV is classified into the OW arenavirus group because of its discovery in Africa, it is phylogenetically distinct from the other OW arenaviruses, including LASV ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, rodents are natural reservoirs of mammarenaviruses, except for Tacaribe virus isolated from an artibeus bat ( 2 , 4 ). A natal multimammate mouse ( Mastomys natalensis ) is known to be the natural host of LASV; however, the reservoirs of LUJV are still unknown ( 5 , 6 ). To establish effective countermeasures against arenavirus infections, it is important to understand the molecular basis of their pathogenicities and host ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Following illness, she was flown to Johannesburg, South Africa to be treated at a private hospital. There, four healthcare workers were exposed and became ill and three died [ 274 ]. Among the hantaviruses, there have been documented cases of person-to-person transmission only for the South American Andes orthohantavirus (ANDV) which have occurred in Argentina and Chile [ 267 , 275 , 276 , 277 , 278 , 279 ].…”
Section: How Do Viruses Spillover From Bats or Rodents To Humans?mentioning
confidence: 99%